(untitled) (Journal of Applied Learning and Teaching, 2023)
This study aims to explore the impact of NVivo, a qualitative data analysis software, from the perspective of graduate students. The study employed a qualitative method, utilizing in-depth interviews with ten graduate students selected through purposive sampling. The data were analyzed using content analysis and NVivo. NVivo has become a valuable asset in the toolkit of graduate students engaged in qualitative research. The software’s ability to organize and analyze vast amounts of qualitative data enhances research efficiency, facilitates collaboration, and supports the production of high-quality research outcomes. However, it is essential to recognize the challenges associated with implementing NVivo and to provide the necessary resources and support to students, ensuring they can fully leverage its potential. As graduate students continue to embrace NVivo in their research endeavors, its impact on qualitative research is expected to grow significantly, advancing the field and contributing to valuable insights and discoveries. This study contributes to the broader field of qualitative research by providing valuable insights into the impact of NVivo from the perspective of graduate students. It enhances our understanding of how NVivo enhances research efficiency, facilitates collaboration, and addresses challenges in implementing the software. These contributions contribute to the advancement of qualitative research methodologies and inform best practices for utilizing NVivo effectively.